Factors affecting the use of online library resources: a case study based on the University of Colombo, Sri Lanka during 2021-2022 - Senanayake, S.G.N.C.; Lankathilake, M.A. (University of Colombo, 2022)
Libraries in the present era are no longer limited to printed materials. There are different online information resources of the libraries which could be accessed by the users even without visiting the libraries. This study was conducted at the library, University of Colombo with the objectives to identify the online library information sources used by students, to examine the usage of library online resources, and to find out the factors affecting the usage of online library resources. The Study population was the total number of undergraduates who used the university’s main library resources during 2021-2022 period. Out of 5456 students a sample of 361 students were selected following stratified random sampling method. Questionnaire survey was conducted to identify the library online resources and the factors that affect the usage of online library resources. Google Analytics data were used to examine the usage of library online resources. The collected data on the usage of online library resources were analyzed using descriptive statistic methods. The factor analysis was used to identify the main factors associated with the usage of online library resources. Findings establish that library website home page, databases, past paper collection in the web, e-books and e-journals are the online resources mostly used by the users. According to the factor analysis, the first six variables represent 87% of the total cumulative values. It indicated first six variables were the most important, it covered 87% of the total cumulative value. Usefulness of online information resources, Awareness, information seeking skills, information quality, easy Access and technical skills and the Internet facility were the factors identified in the study, which affect the use of library online resources. It was recommended that user awareness programmes, sessions on information searching skills and sessions on effective usage of online resources would enhance the use of these resources. Apart from that these factors, google analytic data could be considered when expanding online resources and introducing new services.
Keywords: Online information sources; Internet; E-books; E-journals; Databases